Angiotensin AT2 Receptor is Anti-inflammatory and Reno-Protective in Lipopolysaccharide Mice Model: Role of IL-10 - Fatima, Naureen; Patel, Sanket; Hussain, Tahir (Frontiers in Pharmacology, 2021)
Acute kidney injury (AKI) due to endotoxemic insult is predicted by the infiltration of neutrophils, monocytes and macrophages, and the release of pro-and anti-inflammatory cytokines to the site of injury. Earlier, we have demonstrated the role of angiotensin-II type 2 receptor (AT2R) stimulation in reno-protection in lipopolysaccharide (LPS)-induced inflammation and AKI in C57BL6/NHsd mice. Moreover, AT2R activation has been shown to increase the anti-inflammatory cytokine interleukin-10 (IL-10), its role in AT2R-mediated anti-inflammation and reno-protection is unknown. To address this question, in the present study mice were treated with the AT2R agonist C21 (0.3 mg/kg, intraperitoneally), LPS (5 mg/kg, intraperitoneally), or LPS with C21 pre-treatment with or without neutralizing IL-10 antibody. Treatment with C21 alone caused an increase in the plasma and kidney IL-10 levels, which peaks at 2-hour, and returned to baseline at 6-hour. The C21-induced IL-10 increase was blocked by the AT2R antagonist PD123319 suggesting AT2R’s involvement. LPS treatment caused a profound increase in tumor necrosis factor- (TNF-α) and interleukin-6 (IL-6) and the LPS-induced increase in these cytokines was attenuated by the C21 pre-treatment (1-hour prior LPS) both in the plasma and kidney. Neutralizing IL-10 antibody treatment abrogated the C21-lowering of TNF-α and IL-6 in the kidney but not in the plasma. Similar results as related to the cytokines profiles in all the groups were also observed in the heart and spleen. The alteration in early cytokine profile prompted us to measure the markers of renal function (blood urea nitrogen and urinary creatinine) in order to analyze the effect of IL-10 neutralization. However, it was too early to observe changes in renal function. Therefore, the renal function and injury markers were again measured at 24 hours. Treatment with neutralizing IL-10 antibody attenuated the C21-mediated improvement in indices of the kidney function, but not the biomarkers of renal injury (kidney injury molecule-1 and neutrophil-gelatinase associated lipocalin). Collectively, our data suggest that the involvement of IL-10 in AT2R-mediated anti-inflammation and reno-protection against LPS is complex, mediating the renal cytokine profile and kidney filtration function, but not the plasma cytokine profile and renal injury markers.